2010
DOI: 10.1038/gt.2010.107
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial gene therapy induces regression of hepatic encephalopathy

Abstract: Capillarization of the sinusoid impedes the clearance of neurotoxic substances in liver fibrosis. These events may result in hepatic encephalopathy. Neurological and hepatic features of rats after bile duct ligation (BDL) supplemented with Manganese (BDL+Mn 2+ ) were examined. The 4-week-old BDL rats had elevated levels of ammonia and were concomitantly fed with 1 mg ml À1 of MnCl 2 in drinking water (BDL/Mn +2 ). Five out of fifteen rats were killed and the serum, liver and brain tissue (striatum and substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A decrease has been observed in the DA levels in cortex, hippocampus, striatum and cerebellum along with an increase in the activity of monoamine oxidase B (MAO-B) enzyme following BDL surgery indicating alterations in the dopaminergic system [6]. In addition, BDL rats display a diminution in striatal DA concentration similar to that observed in cirrhotic patients [17]. The concentration of DA metabolite, homovanillic acid, has been shown to be increased in HE patients along with the activity of DA metabolizing enzyme MAO-A and -B as a result of chronic hyperammonemia [18].…”
Section: Introductionmentioning
confidence: 80%
“…A decrease has been observed in the DA levels in cortex, hippocampus, striatum and cerebellum along with an increase in the activity of monoamine oxidase B (MAO-B) enzyme following BDL surgery indicating alterations in the dopaminergic system [6]. In addition, BDL rats display a diminution in striatal DA concentration similar to that observed in cirrhotic patients [17]. The concentration of DA metabolite, homovanillic acid, has been shown to be increased in HE patients along with the activity of DA metabolizing enzyme MAO-A and -B as a result of chronic hyperammonemia [18].…”
Section: Introductionmentioning
confidence: 80%
“…A very recent study using a combinatorial gene therapy strategy (i.e., Adenovirus-MMP-8 plus Adenovirus-human plasminogen activator) proved the therapeutical effect of MMP-8 on liver fibrosis regression, demonstrating that MMP-8 gene insertion improves neuroanatomical and neurochemical conditions in hepatic encephalopathy (Galvez-Gastelum et al, 2011).…”
Section: Neoplastic Diseasesmentioning
confidence: 99%
“…As the first study reported the reduction in TH-IR SNc neurons after porto-caval anastomosis onto rats, an alternative model of HE, in 1991, to date, a few studies have described the neurotoxic effects of HE on the nigrostriatal DA-ergic neurons in vivo ( Cauli et al., 2009 ; El Hiba et al., 2016 ). Among these, a recent study that aimed to reveal the therapeutic action of combinatorial delivery of genes, namely, human plasminogen activator and matrix metalloproteinase-8, used nigrostriatal DA-ergic neurons as the regional target for gene delivery ( Gálvez-Gastélum et al., 2010 ). A few studies in vitro also have shown that DA-ergic neurons are preferentially affected by glutamate toxicity ( Kikuchi and Kim, 1993 ; Casper et al., 2000 ).…”
Section: Discussionmentioning
confidence: 99%